The Financial Fallout: Unraveling Iraq’s Turmoil in the Wake of the U.S. Invasion (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This report examines the financial losses and worsening conditions in Iraq caused by the U.S. war. The study will examine the immediate and long-term economic repercussions of the invasion. The introduction covers the U.S. invasion of Iraq. The event’s significance and Iraq’s post-invasion struggles are highlighted. The issue’s impacts on Iraq’s financial stability include infrastructural destruction, economic stagnation, and government financial constraints. This research will reveal how the U.S. invasion of Iraq has hurt the country’s economy and finances. Economic statistics and topic-related case studies are used. Iraq’s GDP has fallen, its unemployment rate has risen, its currency has depreciated, and its poverty rate has risen. Debt and a full public sector restrict the government from addressing basic needs. The third component of the research addresses the nation’s economic issues and makes solutions to speed up economic recovery. The ideas include reducing debt, reinvesting in infrastructure, seeking outside support, and establishing excellent governance and accountability. After the U.S. invasion of Iraq, the country’s economy has only worsened. Immediate action and international cooperation are needed to overcome these obstacles and give Iraqis a better future.